Silvopastoral systems of the Chaco forests: effects of trees on grass growth - Baldassini, Pablo; Desposito, Cristian Daniel; Piñeiro, Gervasio; Paruelo, José María (Elsevier, 2018)
The area devoted to Silvopastoral systems is increasing worldwide due to its complementary production of beef and wood. Understanding the competition between trees and grasses is critical to identify potential trade-offs in plant production. This article had three objectives: (1) to estimate the seasonal variation of gatton panic (Megathyrsus maximus) productivity and quality in two sites with different annual rainfall, (2) to analyse the effects of tree shadow (“guayacán”, Caesalpinia paraguariensis) on gatton panic above ground primary production (ANPP), and 3) to determine the relative importance of changes in radiation use efficiency (RUE) and incoming radiation (PARi), in defining grass ANPP under trees or exposed to full sunlight. Tree presence reduced gatton panic ANPP by nearly 50%, mainly throughout a reduction in APAR. APAR decrease was not compensated by the RUE increase observed in the wet site and it was exacerbated by a decrease in RUE in the dry site. The decrease in APAR under trees was better explained rather by a decrease in PARi than by the fraction of intercepted PAR. A small increase in shoot grass digestibility was observed under the tree canopy.